KOMITMEN INTERNASIONAL DALAM KERANGKA PERKEMBANGAN DINAMIK UPAYA PENGENDALIAN GLOBAL WARMING - Suparto Wijoyo; Wilda Prihatiningtyas (Yuridika, 2016)
Dynamic of commitment of International Community in the issue of control upon global warming has been developed since 1919 up to present. From available list of international treaties, it can be seen how strong the commitment of global community in the issues of environment, global warming as well as climate change. Unfortunately, it can be concluded, that those international treaties is so fragmented and therefore, is difficult to be implemented comparing with instrument of international environmental law in general. However, political will of national state is the essence to create international agenda. It is because olitical will of the state national is the core to make international agenda .It was because good reasons of a government can bring a good thing for the country and its people , especially again in control global warming So that in this case the state also has a role in realizing environmental sustainability for its people, it is also indirectly a part of the obligation of the state to maintain the stability and survival of the people and the preservation of natural resources in the country, for the welfare and prosperity of all the people .